What drives response time and accuracy in image naming? Moderators in the relationship between number of phonological neighbors and image naming performance - Hashimoto, Naomi; Heuer, Sabine; Cho, Chi C. (Frontiers in Language Sciences, 2025)
Insights into phonological activation patterns during lexical retrieval have been gained from simple image naming and picture word interference paradigm (PWIP) studies. Simple image naming studies allow for the manipulation of phonological variables, such as the number of phonological neighbors (NPN). PWIP studies allow for the manipulation of the relationship between a target and distractor, considering the effects of lexical co-activation. PWIP studies have reported a phonological facilitation effect when phonologically related stimuli are introduced during certain time-frames. We conducted a series of experiments in young, neurotypical adults using images that were validated across a number of measures known to affect naming performance. A simple image naming experiment (Experiment 1) was followed by two PWIP experiments, where the SOAs were set at +300 ms (Experiment 2) and +150 ms (Experiment 3) and images were paired with phonologically related or unrelated distractors. Across all experiments, we found that NPN was modulated by other variables such as age-of-acquisition, and image familiarity. While a main effect of distractor type was obtained for the PWIP experiments, there was no interaction between NPN and distractor type. The findings highlight the complex nature of NPN, and the subtle influences that NPN has on picture naming process.